Genome-Wide Evolution and Comparative Analysis of Superoxide Dismutase Gene Family in Cucurbitaceae and Expression Analysis of Lagenaria siceraria Under Multiple Abiotic Stresses - Rehman, Shamsur; Rashid, Arif; Manzoor, Muhammad Aamir; Li, Lingling; Sun, Weibo; Riaz, Muhammad Waheed; Li, Dawei; Zhuge, Qiang (Frontiers in Genetics, 2022)
Superoxide dismutase (SOD) is an important enzyme that serves as the first line of defense in the plant antioxidant system and removes reactive oxygen species (ROS) under adverse conditions. The superoxide dismutase (SOD) protein family is widely distributed in the plant kingdom and plays a significant role in plant growth and development. However, the comprehensive analysis of the SODs gene family has not been conducted in Cucurbitaceae. Subsequently, 43 SOD genes were identified from Cucurbitaceae species (Citrullus lanatus, Cucurbita pepo, Cucumis sativus, Lagenaria siceraria, Cucumis melo). According to evolutionary analysis, SOD genes were divided into Eight subfamilies (Ⅰ, Ⅱ, Ⅲ, Ⅳ, Ⅴ, Ⅵ, Ⅶ, VIII). The gene structure analysis exhibited that the SOD genes family had comparatively preserved exon/intron assembly while motif as well. Phylogenetic and structural analysis revealed that functional divergence of Cucurbitaceae SODs gene family. Further, functional analysis of GO annotation and microRNAs demonstrated that these genes involved in the growth and regulation of SOD genes. Promoter regions of the SOD family revealed that most cis-elements were involved in plant developments, stress response, and plant hormones. Evaluation of the gene expression showed that most SOD genes were expressed in different tissues (root, flower, fruit, stem, and leaf). Finally, the expression profiles of eight LsiSOD genes analyzed by qRT-PCR, suggested that these genetic reserves responded to drought, saline, heat, and cold stress. These findings laid the foundation for further study of the role of the SOD gene family in Cucurbitaceae. Also, they provided the potential for its use in the genetic improvement of Cucurbitaceae.